Adult drama : and other essays - Beach, Natalie (Hanover Square Press, 2023)
"The writer of the viral New York Magazine piece 'I Was Caroline Calloway' presents an absurdist and comical memoir-in-essays about the frenzied journey to adulthood in a world gone mad"--